(untitled) - United Nations Population Fund ( UNFPA ) (Hà Nội, 2006)
Executive summary: Registration and migrant status; the diffilulties faces by migrants; the effects of migrant status on housing conditions; the effects of migrant stastus on labour market outcomes; migrant networks, labour market outcomes and housing; policy implication.
Keywords: Migration, Internal,Emigration and immigration,Migration, Internal; Statistics,Research,Developing countries; Viet Nam